SAVI-Based Interactive Multimedia Using Macromedia Flash for Comparative Material for Fifth Grade Elementary School Students - Nurul Hidayah; Yuniawatika; Siti Mas'ula (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Mathematics learning in fifth grade still faces challenges in improving the understanding of the concept of comparison. Therefore, an innovative and interactive learning medium is needed. The purpose of this study is to create interactive multimedia based on SAVI using Macromedia Flash comparison material in fifth-grade elementary schools, which is valid, practical, and effective. This research is a type of R&D research model, as described by Borg & Gall, which consists of ten stages. There are 38 fifth-grade elementary school students as research subjects. Media and material experts measure validity data. Practicality data is measured based on teacher and student responses. Data are obtained through observation, interviews, questionnaires, and tests. Data analysis uses qualitative and quantitative techniques. The results of the study show that the product is highly valid, with values of 92.04% and 97.91%, and highly practical, with a value of 97.75%. Meanwhile, the effectiveness test of the final product revealed a difference in student learning outcomes before and after using interactive multimedia based on SAVI through Macromedia Flash. It was concluded that SAVI-based interactive multimedia, developed using Macromedia Flash, was effective in improving the understanding of the concept of comparison among fifth-grade students. This study suggests that students demonstrated a significant improvement in their understanding of the concept of comparison after using interactive multimedia.